Sistem Informasi Surat Keluar dan Surat Perintah Tugas Berbasis Web Menggunakan Metode Rapid Application Development - Fadilah Maysarah Nasution; Arie Linarta; Masrizal Masrizal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Information technology has been widely applied in various sectors, including in supporting government administration activities. One activity that is still carried out manually is the process of making outgoing letters and task orders. Problems that arise include the length of the letter-making process, errors in formatting, and dependence on certain staff in preparing letters. The research was conducted at the Dumai City Social and Community Empowerment Service, sepecially in the Social Rehabilition Division. This research aims to build a web-based information system that can automate the process of making outgoing letters and task orders, making it faster, more efficient, and minimal errors. Data collection techniques used in this research include observation, interviews, and dicumentation studies. System development is carried out using the Rapid Application Development (RAD) method, which focuses on rapid development by involving users. Testing of this system will be carried out using the black box testing method. The results showed that the information system built was able to produce outgoing letters and task orders automatically using templates that had been prepared. Users only need to fill in data through the available forms, so that the process of making letters becomes faster, more precise and easier to use. With this system, it s expected that the mail administration process in the Social Rehabilitation Division will be more efficient can be more effective and efficient, and reduce the potential for errors in letter creation.